THE STUDENT FACTOR ANALYSIS CHOOSING BIOLOGY AS A OPTIONS SUBJECT OF COMPUTER-BASED NATIONAL EXAMINATION - Puspitasari, Ratna Dewi; Puspitasari, Ratna Dewi; Priyono, Bambang; Ridlo, Saiful (Journal of Biology Education, 2019)
This study aims to analyze the factors that influence learners in choosing Biology as the subject of choice of UNBK and analyze the most dominant factor in influencing learners choose Biology as the preferred subject of UNBK. This research is a mixed method research using sequential mix method with qualitative-quantitative sequential explanatory strategy. The population in this study are students of science majors class XII who choose Biology in SMA N 1 Pecangaan and SMA N 1 Jepara, amounting to 208 learners. The technique of sampling data using random sampling technique. Determination of the number of samples using Isaac and Michael formula with a 95% confidence level, so that obtained at least 131 samples from 208 members of the population. The results of this study indicate: (1) There are 9 factors that influence the Friends and Parents, Interests and Motivation, Ideals and Profession of Parents, Ability, Teacher and Parents, School Environment, Perception, and Interest and Achievement. The most dominant factor affecting is Friends and Parents with an eigenvalue of 6,922 which can explain the variant variation of 24.723% of cumulative variance percentage of 71,675%.